2018
DOI: 10.1038/s41467-018-05200-w
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic transition at contacts key to maximizing fill factor and performance of organic solar cells

Abstract: While thermodynamic detailed balance limits the maximum power conversion efficiency of a solar cell, the quality of its contacts can further limit the actual efficiency. The criteria for good contacts to organic semiconductors, however, are not well understood. Here, by tuning the work function of poly(3,4-ethylenedioxythiophene) hole collection layers in fine steps across the Fermi-level pinning threshold of the model photoactive layer, poly(3-hexylthiophene):phenyl-C61-butyrate methyl ester, in organic solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 52 publications
(63 reference statements)
2
57
0
Order By: Relevance
“…This is an interesting finding and demonstrates the ability of solution‐processed MX 2 nanosheets to alter the WF of the ITO electrode. The significant WF shift is expected to lead to the formation of a better hole extracting contact with the BHJ layer as compared to PEDOT:PSS …”
Section: Summary Of Photovoltaic Operating Parameters For Pbdb‐t‐sf:imentioning
confidence: 99%
“…This is an interesting finding and demonstrates the ability of solution‐processed MX 2 nanosheets to alter the WF of the ITO electrode. The significant WF shift is expected to lead to the formation of a better hole extracting contact with the BHJ layer as compared to PEDOT:PSS …”
Section: Summary Of Photovoltaic Operating Parameters For Pbdb‐t‐sf:imentioning
confidence: 99%
“…The fill factor ( FF ) [52,53,54,55], as mentioned above, depends on the series resistance, shunt resistance and diode. However, these also depend on a large number of factors that interact with each other intricately and for this reason the FF is more complex and less understood than the V oc and J sc [47,56,57,58]. Previous studies have shown that variables such as the blend composition, the blend morphology, the regioregularity of the conjugated polymer and the thickness of the BHJ influence significantly the FF affecting R s and R sh [52].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of emerging photovoltaic technologies based on organic materials, device modeling has been extensively used to not only develop a deeper understanding of the physical principles governing the device function, [6][7][8] but also as a tool for optimizing the device structure in order to enhance its performance. [9][10] Similarly, albeit to a lesser degree, device simulations have also been applied to colloidal quantum dot photovoltaics. 11 Since the advent of perovskite photovoltaics, significant experimental efforts have been devoted to enhancing the device power conversion efficiency (PCE), reaching remarkable improvements in just a decade.…”
Section: Main Textmentioning
confidence: 99%